"Scent of a fruit fly": Cuticular chemoprofiles after mating in differently fed Drosophila melanogaster (Diptera: Drosophilidae) strains. Issue 3 (12th January 2022) - Pavković‐Lučić, Sofija; Trajković, Jelena; Miličić, Dragana; Anđelković, Boban; Lučić, Luka; Savić, Tatjana; Vujisić, Ljubodrag
Abstract: In the world of complex smells in natural environment, feeding and mating represent two important olfactory‐guided behaviors in Drosophila melanogaster (Diptera: Drosophilidae). Diet affects the chemoprofile composition of the individuals, which, indirectly, may significantly affect their mating success. In this study, chemoprofiles of recently mated flies belonging to four D. melanogaster strains, which were fed for many generations on different substrates (standard cornmeal—S strain; banana—B strain; carrot—C strain; tomato—T strain) were identified and quantified. In total, 67 chemical compounds were identified: 48 compounds were extracted from males maintained on banana and carrot, and 47 compounds from males maintained on cornmeal and tomato substrates, while total of 60 compounds were identified in females from all strains. The strains and the sexes significantly differed in qualitative nature of their chemoprofiles after mating. Significant differences in the relative amount of three major male pheromones ( cis ‐vaccenyl acetate—cVA, ( Z )‐7‐pentacosene, and ( Z )‐7‐tricosene) and in female pheromone ( Z, Z )‐7, 11‐nonacosadiene among strains were also recorded. Furthermore, multivariate analysis of variance (MANOVA) pointed to significant differences between virgin and mated individuals of all strains and within both sexes. Differences in some of the well known sex pheromones were also identified when comparing their relative amount before and after mating. The presence of typical male pheromones in females, and vice versa may indicate their bidirectional transfer during copulation. Our results confirm significant effect of mating status on cuticular hydrocarbon (CHC) phenotypes in differently fed D. melanogaster flies. Abstract : Cuticular hydrocarbons of mated males and females belonging to four differently fed Drosophila melanogaster strains were extracted and identified.